Security Issues of Wimax - Santosh, V. Venkata; Maram, Balajee; Kumar, V. (International Journal For Research In Advanced Computer Science And Engineering, 2016)
WiMAX: worldwide interoperability for microwave access is newly emerging technology, which is under developing. The main difference from the Wi-Fi to WiMAX is the range i.e. it covers more area than that of Wi-Fi. But in the development process of the newly emerging technology also there are different issues to be considered in order to eliminate threats to security. The actual security techniques have been implementing in the physical and mac layers. So the threats to security also may occur in these two layers only. In this paper we will address the different types of layers and the functions of each layer which is other than protocol architecture, the different types of security solutions, and what are the different types of threats to physical and mac layers.